A comparison of outcomes after percutaneous nephrolithotomy in children and adults: A matched cohort study. Issue 5 (October 2015) - Lee, Linda C.; Violette, Philippe D.; Tailly, Thomas; Dave, Sumit; Denstedt, John D.; Razvi, Hassan
Summary: Introduction: Percutaneous nephrolithotomy (PCNL) has surpassed open stone surgery as the operation of choice for large and complex stone burdens (figure). Although the procedure was developed in adults, its principles have been extrapolated to children. There is a paucity of literature comparing outcomes of PCNL in adults and children for similar stone burdens. Objective: The purpose of this study was to evaluate outcomes following PCNL among children and adults with similar stone burdens. Patients and methods: Data on patient characteristics and outcomes for 2196 consecutive patients undergoing PCNL at a single institution were collected prospectively from January 1992 to July 2013. Thirty-one pediatric patients undergoing 39 PCNLs were identified. Each pediatric PCNL was matched in a ratio of 1:4 to adult PCNLs by year of surgery and stone burden characteristics (staghorn, partial staghorn, number of stones). All PCNLs were performed by two fellowship-trained endourologists who operate on both adult and pediatric patients. Ultrasonic lithotripsy was used primarily. The primary outcome measure was stone-free rate (SFR) at hospital discharge. Secondary outcomes included the need for second-look nephroscopy, length of hospital stay, complication rate, and blood transfusion rate. The Student t test was used for continuous variables and the Fisher exact for categorical variables. Results: The median age for the pediatric group was 13.9 ± 4.30 years and for the adult group was 55.4 ± 15.1 years. Pediatric patients tended to present with metabolic stones, with no difference in rates of infection stones. No difference was found in SFR at time of hospital discharge (86.1% vs. 86.4%, p = 0.2). More pediatric patients required a second access tract than adult patients (15.4% vs. 4.52%, p = 0.02). There was no significant difference in the need for second-look nephroscopy, length of stay, or complication rates (overall and by Clavien classification subgroup) between both groups. The rates of blood transfusion were low in both groups (0% vs. 0.6%, p = 0.80). Discussion: There was no difference in primary and secondary outcomes among children compared with adults undergoing PCNL in our study. The outcomes reported in this study were similar to published literature. A limitation of this study is the low number of pediatric patients. However, it is unique to have a single-center study that compares PCNL outcomes in both adult and pediatric patient and accounts for stone burden characteristics. Conclusions: Although principles of PCNL were developed in adults, this study affirms the safety and efficacy of PCNL in both pediatric and adult patients. Figure Preoperative and postoperative kidney ureter bladder radiograph of a child who underwent a simultaneous right PCNL and endoscopic removal of a watch battery.